1997
DOI: 10.1038/bjc.1997.576
|View full text |Cite
|
Sign up to set email alerts
|

Differential level of DSB repair fidelity effected by nuclear protein extracts derived from radiosensitive and radioresistant human tumour cells

Abstract: Summary A cell-free plasmid reactivation assay was used to determine the fidelity of DNA double-strand break (DSB) repair in a panel of eight DSB repair-proficient human tumour cell lines. Nuclear protein extracts derived from radiosensitive tumour cells were less capable of correctly rejoining EcoRI-induced DSBs than were similar extracts from radioresistant tumour cells. Linear regression analysis suggests that there was a significant (r2 = 0.84, P = 0.001, d.f. = 6) correlation between the fidelity of DSB r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…It has been suggested that restriction endonucleasegenerated DSBs act as substrates for proteins that are involved in the (abnormal) conversion of DSBs into chromosomal aberrations (Bryant and Liu, 1994). This conclusion is supported by the fact that ataxia telangiectasia (AT) and irs cells exhibit high DSB misrejoining activity (Cox et al, 1984;Thacker and Ganesh, 1990;Ganesh et al, 1993;Powell et al, 1993;Lou et al, 1996), and generate high levels of chromatid-type aberrations in response to restriction endonuclease-induced DSBs (Liu and Bryant, 1993;Bryant, and Liu, 1994).The biochemical basis for the differential level of DSB misrejoining activity in nuclear protein extracts from radiosensitive and radioresistant tumour cells is presently unknown, although we have shown that the high DSB misrejoining activity in radiosensitive tumour cells was not a consequence of non-specific endonuclease activity but rather due to an increase in non-conservative DSB rejoining activity that results in losses of between 40 and 440 bp of DNA (Britten et al, 1997). Furthermore, previous studies have Modification of non-conservative double-strand break (DSB) rejoining activity after the induction of cisplatin resistance in human tumour cells…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…It has been suggested that restriction endonucleasegenerated DSBs act as substrates for proteins that are involved in the (abnormal) conversion of DSBs into chromosomal aberrations (Bryant and Liu, 1994). This conclusion is supported by the fact that ataxia telangiectasia (AT) and irs cells exhibit high DSB misrejoining activity (Cox et al, 1984;Thacker and Ganesh, 1990;Ganesh et al, 1993;Powell et al, 1993;Lou et al, 1996), and generate high levels of chromatid-type aberrations in response to restriction endonuclease-induced DSBs (Liu and Bryant, 1993;Bryant, and Liu, 1994).The biochemical basis for the differential level of DSB misrejoining activity in nuclear protein extracts from radiosensitive and radioresistant tumour cells is presently unknown, although we have shown that the high DSB misrejoining activity in radiosensitive tumour cells was not a consequence of non-specific endonuclease activity but rather due to an increase in non-conservative DSB rejoining activity that results in losses of between 40 and 440 bp of DNA (Britten et al, 1997). Furthermore, previous studies have Modification of non-conservative double-strand break (DSB) rejoining activity after the induction of cisplatin resistance in human tumour cells…”
mentioning
confidence: 75%
“…The biochemical basis for the differential level of DSB misrejoining activity in nuclear protein extracts from radiosensitive and radioresistant tumour cells is presently unknown, although we have shown that the high DSB misrejoining activity in radiosensitive tumour cells was not a consequence of non-specific endonuclease activity but rather due to an increase in non-conservative DSB rejoining activity that results in losses of between 40 and 440 bp of DNA (Britten et al, 1997). Furthermore, previous studies have Modification of non-conservative double-strand break (DSB) rejoining activity after the induction of cisplatin resistance in human tumour cells…”
mentioning
confidence: 83%
See 3 more Smart Citations